Angiotensin-converting enzyme 2 gene targeting studies in mice: mixed messages - Gurley, Susan B.; Coffman, Thomas M. (Experimental physiology, 2008)
As a major regulator of blood pressure homeostasis, the reninâangiotensin system (RAS) has been the subject of extensive scientific investigation. While the RAS was first discovered more than 100 years ago, several novel components of the system have been identified only in the last decade. One of these newer members of the RAS family is angiotensin-converting enzyme 2 (ACE2). Among the approaches used to establish a physiological role for ACE2 has been the generation of ACE2-null mouse lines using homologous recombination in embryonic stem cells. In the literature, there have been at least three lines of ACE2 knockout mice generated by gene targeting by different investigative groups. Interestingly, there are significant differences in some of the reported phenotypes of these distinct lines, especially with regard to their cardiovascular physiology. In this paper, we will review the results of published experiments using these ACE2-null mouse lines, highlighting similarities and differences in these studies and summarizing their contributions to our understanding of the physiological functions of this novel member of the RAS.